Prácticas sexuales y anticoncepción en puérperas en un Hospital de tercer nivel de atención de Paraguay, 2017 - María de los Ángeles Giménez; Anibal Kawabata; Carlos Miguel Rios-Gonzalez (Instituto Nacional de Salud (INS), 2019)
Introduction:The fact of restarting the sexual life after childbirth constitutes a source of tension and / or emotional stress in some women, which can lead to long-term conflicts in the life of a couple, largely influenced by physical changes and Emotional that occur. Objective: Describe the sexual practices and contraception of the puerperal women of a third level hospital in Paraguay during 2017. Methodology: Descriptive, cross-sectional study, with probabilistic sampling of consecutive cases, which showed 84 women from the Regional Hospital of Coronel Oviedo, 2017. Results:84 women were included, the percentage that resumed sexual intercourse was 42.86% (n = 36), the average time being 8 ± 5.68 weeks; 64.29% (n = 54) admitted to having performed non-coital sexual practice, at a time of onset of 2 ± 2.96 weeks. The main reasons for sexual intercourse were due to desire and personal comfort 47% (n = 17) and request of the couple 33% (n = 12), the reasons why they did not restart were for fear of feeling pain 30% (n= 25) and for fear of a new pregnancy 20% (n = 20). Of the women who performed non-coital sexual practice, 87% (n = 47) practiced only kisses and caresses with erotic intent. The majority used the 38% quarterly hormonal injection as a contraceptive method for resumption (n = 14). 44.05% (n = 37) used the quarterly hormonal injection as a modern contraceptive method. Conclusion:The sexual practices and contraception of the puerperal women of the Regional Hospital of Coronel Oviedo during the month of October 2017 were: less than half of the women resumed sexual intercourse in an average time of 8 weeks, for desire and comfort personal; while the restart of non-coital sexual practices was greater than half, in a time of 2 weeks. The main modern contraceptive method used was the quarterly hormonal injection.